Study of Women's Space in Bagas Godang In the Village of Wek II Batang Toru South Tapanuli - Sandra Oktavia Skb; Cut Azmah Fithri; Yenny Novianti; Erna Muliana (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The traditional house in South Tapanuli is an architecture with a distinctive shape with a type of house on stilts. One such building is bagas godang. This building functions as a residence or residence of the king, also functions as a place for holding traditional ceremonies, and as a place of protection for members of the community. The women's room in the godang bagas is a place for women's activities. Currently the space has changed its function. This study aims to re-describe women's space as a private space inside the godang bagas. The method used in this study is descriptive qualitative by way of observation, interviews and documentation. The results obtained are that several rooms inside the godang bagas are women's rooms. These spaces include a bedroom, kitchen and circulation room. This space is used by women in their daily activities. The women's room is very special in the house, a space that makes women feel at home and comfortable.